Lower serum zinc concentration despite higher dietary zinc intake in athletes: A systematic review and meta-analysis - Chu, A.; Holdaway, C.; Varma, T.; Petocz, P.; Samman, S. (Sports Medicine, 2018)
Background: Zinc is an essential trace element that has been implicated in numerous biological functions, including immunity, energy metabolism and antioxidative processes. Recent evaluations of the literature have provided evidence of significant acute changes in zinc metabolism following a bout of aerobic exercise. Objective: The aim of this study was to determine the zinc status of trained athletes compared with control populations, as described in cross-sectional studies. Design: We conducted a systematic literature search of the PubMed, Scopus, SPORTDiscus and Cochrane Library electronic databases from inception to 28 January 2016 to identify cross-sectional studies that determined the zinc status of athletes compared with a control population. Meta-analysis of the differences in serum zinc concentration and dietary zinc intake between groups were conducted. Results: Twelve studies were included in the systematic review. Of the included studies, nine and eight studies provided sufficient data for the meta-analysis of serum zinc concentration and dietary zinc intake, respectively. Serum zinc concentration was significantly lower in athletes [- 0.93 µmol/L, 95% confidence interval (CI) - 1.62 to - 0.23] despite significantly higher dietary zinc intake compared with the control population (2.57 mg/day, 95% CI 0.97-4.16). Data on erythrocyte and urinary zinc from the included studies were insufficient for meta-analysis. Conclusions: Despite higher total dietary zinc intake, athletes generally have lower serum zinc concentration, which suggests that athletes have higher requirement of zinc than those who are physically inactive. Further investigations of zinc metabolism during exercise and dietary zinc requirement in active populations are needed to establish evidence-based recommendations.